Efeitos da estimulação transcraniana por corrente contínua no desempenho cognitivo de atletas de voleibol - Ianni, Renata Miranda [UNIFESP] (2017)
Objective: To compare intimate partner violence (IPV) prevalence rates in 2006 and 2012 in a nationally representative household sample in Brazil. The associations between IPV and substance use, depression, suicidal ideation and attempts, lack of social support and HIV-STD infection were also investigated. The analyzes detailed results for victims, offenders, involved in bidirectional IPV, men and women. Methods: This is a cross-sectional study, based on data from two waves (2006/2012) of the Brazilian National Alcohol and Drugs Survey (BNADS). IPV was assessed using the Conflict Tactic Scale-R. to the Depression, the CES-D scale (Center for Epidemiological Studies Depression Scale); AUDIT (Alcohol Use Disorders Test) for the consumption of alcohol and the questionnaire APMS (Adult Psychiatric Morbidity Survey - England) for the use of tobacco; illicit substances and Network Social Support. Weighted prevalence rates and adjusted logistic regression model were calculated for the odds ratio (odds). Results: Prevalence rates of IPV victimization decreased significantly, especially among women. The rates of IPV perpetration also decreased significantly for the overall sample and in men), as well as the rates of bidirectional violence (by individuals who were simultaneously victims and perpetrators of violence). Alcohol increased the likelihood of being a victim and perpetrator of IPV. Use of illicit drugs increased up to 4.5 times the likelihood of being a perpetrator. The associations between IPV and depressive symptoms, suicidal ideation and attempt and STD/HIV-positive were significant for victims, perpetrators and involved with bidirectional violence. Conclusions: In spite of the significant reduction in most types of IPV between 2006 and 2012, violence perpetrated by women was not significantly reduced, and the current national rates are still high. Further, this study suggests that use of alcohol and other psychoactive drugs plays a major role in IPV as well as the outcomes of depression, suicide attempts and STD/HIV infection. Prevention initiatives should take into account the misuse of drugs and these outcomes.